2011
DOI: 10.1007/s11199-011-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender Conceptualizations in Female High School Seniors: Relationships with Global Self-Worth and Multiple Measures of Body Image

Abstract: This study was conducted to determine if genderrole conceptualizations in adolescent girls were related to their global self-worth and several dimensions of their body image. Self-report surveys were administered to 335 predominantly Caucasian Grade 12 girls from religiouslybased high schools in the midwestern part of the United States. It was hypothesized that adolescent females' gendertyping of themselves as well as their gender-related attitudes towards others would be significantly, and possibly divergentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Adolescence is a time of significant growth and development in terms of perceptions, behaviours, attitudes and values (Bowker et al, 2003;Horn et al, 2011;Russell, 2004). The results of this study found that participants were highly influenced by their peers in relation to their participation in TMS.…”
Section: Peer Influencementioning
confidence: 63%
See 2 more Smart Citations
“…Adolescence is a time of significant growth and development in terms of perceptions, behaviours, attitudes and values (Bowker et al, 2003;Horn et al, 2011;Russell, 2004). The results of this study found that participants were highly influenced by their peers in relation to their participation in TMS.…”
Section: Peer Influencementioning
confidence: 63%
“…Self-esteem, self-efficacy and body image are related strongly to whether females feel they are conforming to their gender roles as based on gender role expectations (Horn, Newton & Evers, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Even players who are not heavily invested in the game may come to start associating their own self-worth with ingame stats: she might come to think about herself in terms of "real life stats" related to body image and successful performance of normative gender expectations. Many women across differing ethnicities, cultures and countries already believe that their perceived physical appearance is an indicator of their self-worth (Horn et al 2011). The game is reinforcing pre-existing and culturally instilled genderoriented anxieties for a new generation of Japanese girls -as well as others who might play it.…”
Section: The Intricacies Of Datingmentioning
confidence: 99%
“…14 Additionally, shape-and weightbased self-esteem is now considered as a central substrate of body image and global self-esteem. 15 The relationship between body image and self-esteem among youth has been well documented in several studies, [16][17][18] and it is present regardless of age and sex. 19 Furthermore, the association between body image and self-esteem is more prominent in comparison with those between self-esteem and other domains of life experience across age groups and countries.…”
mentioning
confidence: 97%